Knockdown of Phytophthora cinnamomi gip gene by iRNA - Chahed, Abdessalem (2018)
Ink Disease is considered one of the most important causes of the decline of chestnut orchards. The break in yield of Castanea sativa Mill is mainly caused by Phytophthora cinnamomi one of the most aggressive and widespread plant pathogen causing enormous economic losses and up to now no efficient treatments are available to fight these pathogens. Because of the importance of chestnut at economical and ecological levels especially in Portugal, it becomes essential to explore the molecular mechanisms that determine the interaction between Phytophthora species and host plants through the study of GIP protein produced by P.cinnamomi during the infection.